# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime }-2 y^{\prime }+y = {\mathrm e}^{t} \ln \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = {\mathrm e}^{t} \ln \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 t y^{\prime }+t^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }-5 t y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+7 x y^{\prime }+8 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }+5 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}5 x^{2} y^{\prime \prime }-x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-7 x y^{\prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-7 x y^{\prime }+15 y = 8 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }-3 y = x \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}\left (2 x^{2}-1\right ) y^{\prime \prime }+2 x y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}3 x y^{\prime \prime }+11 y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }+5 x y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-7 x y^{\prime }+\left (-2 x^{2}+7\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x \left (1-x \right ) y^{\prime \prime }+\left (2 x +1\right ) y^{\prime }+10 y = 0
\] |
✓ |
✓ |
|
\[
{}x \left (1+x \right ) y^{\prime \prime }+\left (1-2 x \right ) y^{\prime }-10 y = 0
\] |
✓ |
✓ |
|
\[
{}t \left (y y^{\prime \prime }+{y^{\prime }}^{2}\right )+y y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}4 x^{\prime \prime }+9 x = 0
\] |
✓ |
✓ |
|
\[
{}9 x^{\prime \prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+64 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+100 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+16 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+256 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+9 x = 0
\] |
✓ |
✓ |
|
\[
{}10 x^{\prime \prime }+\frac {x}{10} = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+3 x = 0
\] |
✓ |
✓ |
|
\[
{}\frac {x^{\prime \prime }}{32}+2 x^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}\frac {x^{\prime \prime }}{4}+2 x^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{\prime \prime }+2 x^{\prime }+8 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+13 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+20 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = \left \{\begin {array}{cc} 1 & 0\le t <\pi \\ 0 & \pi \le t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = \left \{\begin {array}{cc} \cos \left (t \right ) & 0\le t <\pi \\ 0 & \pi \le t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = \left \{\begin {array}{cc} t & 0\le t <1 \\ 2-t & 1\le t <2 \\ 0 & 2\le t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+13 x = \left \{\begin {array}{cc} 1 & 0\le t <\pi \\ 1-t & \pi \le t <2 \pi \\ 0 & 2 \pi \le t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = \cos \left (\frac {9 t}{10}\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = \cos \left (\frac {7 t}{10}\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+\frac {x^{\prime }}{10}+x = 3 \cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = 6, y^{\prime }\left (t \right ) = \cos \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = x \left (t \right ), y^{\prime }\left (t \right ) = 1]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = 0, y^{\prime }\left (t \right ) = -2 y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = x \left (t \right )^{2}, y^{\prime }\left (t \right ) = {\mathrm e}^{t}]
\] |
✓ |
✓ |
|
\[
{}[x_{1}^{\prime }\left (t \right ) = -3 x_{1} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 1]
\] |
✓ |
✓ |
|
\[
{}[x_{1}^{\prime }\left (t \right ) = -x_{1} \left (t \right )+1, x_{2}^{\prime }\left (t \right ) = x_{2} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = -3 x \left (t \right )+6 y \left (t \right ), y^{\prime }\left (t \right ) = 4 x \left (t \right )-y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = 8 x \left (t \right )-y \left (t \right ), y^{\prime }\left (t \right ) = x \left (t \right )+6 y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = -x \left (t \right )-2 y \left (t \right ), y^{\prime }\left (t \right ) = x \left (t \right )+y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = 4 x \left (t \right )+2 y \left (t \right ), y^{\prime }\left (t \right ) = -x \left (t \right )+2 y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = y \left (t \right ), y^{\prime }\left (t \right ) = -x \left (t \right )+1]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = y \left (t \right ), y^{\prime }\left (t \right ) = -x \left (t \right )+\sin \left (2 t \right )]
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-3 x^{\prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+6 x^{\prime }+9 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+16 x = t \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = {\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y+3 y^{{1}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {x -y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {x^{2}-y}-x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {1-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1+y}{x -y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (y\right )-\cos \left (x \right )
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = 1-\cot \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (3 x -y\right )^{{1}/{3}}-1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x y\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime }+x y = 2 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x +y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y-x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x}{2}-y+\frac {3}{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (y-1\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (y-1\right ) x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (x -y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y-x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}+2 x -y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1+y}{x -1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +y}{x -y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1-x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x -y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}+y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {y}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x +y
\] |
✓ |
✓ |
|